PERANAN SERBUK BENTONIT TERHADAP SIFAT MEKANIS DARI KOMPOSIT RESIN POLIESTER BQTN 157-EX - Rihayat, Teuku (Jurnal Sains dan Teknologi Reaksi, 2008)
Composite are mixture difference materials or has more produces characterize and characterization it doesn’t produces in main materials. Resin polyester BQTN 157-EX are part of dominant (major) into composite the function as matrix and bentonite are part of not dominant (minor) into composite the fuction as filler. The first reseach for bentonite processed that source from material anorganic and hydrophilic characteristic was done. This examination was done with using tensile strenght equipment. The result showed, in 3,5% nanocomposite, mass of bentonite and 300 mesh of particle sizes produced a tensile strength of 197,57 Mpa, elongation of 24% and 0.80 Joule of Impact. This case more better if compared with virgin resin polyester, that produce 104,92 Mpa of tensile strenght, 13,32% of elongation and 0,21 Joule of Impact.Keywords : Poliester BQTN 157-EX, Composites, Mechanic Properties